Collective directional movement and the perception of social cohesion. (3rd January 2020) - Wilson, Stuart; Mansour, Jamal K.
Abstract : We argue that perceivers associate collective directional movement – groups moving from one place to the next – with higher levels of social cohesion. Study 1 shows that pairs are rated as being more cohesive when described as engaging in directional movement compared to non‐directional activities. Study 2 replicates this finding using film clips. Study 3 reveals that the proximity of directionally moving dyads is a better predictor of perceived cohesion than behavioural synchrony. Study 4 replicates the original finding and reveals that perceptions of common fate and shared goals both contribute to the effect, with the former having more predictive power than the latter. We suggest that collective directional movement is an invariant part of social environments and is utilized by perceivers to make inferences about social dynamics.